Pengaruh Model Problem Based Learning Terhadap Keterampilan Berpikir Kreatif Siswa Kelas V SD - Mufarrohah, Mufarrohah; Setyawan, Agung (JOURNAL OF EDUCATION FOR ALL, 2024)
This research aims to determine the significant influence of the application of the problem based learning model on the creative thinking skills of V grade elementary school students. This research is experimental research using a Nonequivalent Control Group Design research design. Sampling was taken using a non-probability sampling technique, saturated sampling type. The research sample was 30 students, namely 15 students in the experimental group and 15 students in the control group. Data was collected using interviews, observation, tests and documentation. The research results show that the problem based learning model has an effect on students' creative thinking skills. The instrument trials used were validity and reliability tests, while data analysis used normality tests and homogeneity tests. Hypothesis testing using the independent t-test. The calculated significance value is 0.000. Based on the test criteria if the Sig. < 0.05 (0.000 < 0.05), then H0 is rejected and Ha is accepted, which means there is an influence on the application of the problem based learning model on the creative thinking skills of V grade elementary school students.